Major livestock health problems in market oriented livestock development in Mieso woreda, western Harerghe, Ethiopia - Asebe, G. (Addis Ababa University, 2007)
A survey was carried out to study major livestock health constraints in four peasant association of Mieso Woreda, Eastern Ethiopia, from November, 2006 to April, 2007. A questionnaire survey was carried out with the main objectives of assessing major health problems and characterization of the production system of livestock. The study carried out on 80 households to collect livestock health problems in market oriented livestock development, livestock production system and associated information by giving emphasis on livestock health. All livestock owned by households were study animals. Four PAs were selected from a total of 49 PAs purposively. Households (N=80) were randomly selected and interviewed from the four PAs 20 from each. Group discussion and observational studies were also conducted. 10-12 key respondents were selected for each PAs by the respective DAs and discussed for one hour. Clinical observation also made from November, 2006 to March, 2007. The production system was found to be mixed type with main livestock of cattle and goats. Most of the respondents were found to be non-educated. Health problems were mentioned and ranked by the respondents. The percentages of diseases were calculated based on the respondent frequency. Major livestock health problems in cattle are anthrax, blackleg, Pasteurellosis, FMD, enteritis, predators, tick and others; in camel pneumonia, skin disease, GIT parasite, enteritis and others; in small ruminants enteritis, Orf, circling disease, pasteurellosis, predators and others; in equines respiratory diseases, colic, GIT parasites, local swelling and others. The poultry respondents (n=45) mentioned and ranked NCD (Fengil), others were lice, mites, and fleas.